Mobiles Internet im Unternehmenskontext Webtechnologien als technische Basis für Geschäftsanwendungen auf mobilen Endgeräten - Christmann, Stefan (Universitätsverlag Göttingen, 2012)
The mobile Internet - understood as the usage of Internet services and protocols over wireless networks - is a technology which can be of beneficial use in companies. So far and in contrast to the use by private customers this area is still under development, which can be explained through the special conditions of IT-implementation in enterprises.Stefan Christmann therefore analyzes usage potentials and challenges of this technology and describes technical solutions to enable the application of mobile Internet in enterprises and to make it more economical. In the area of application development, the book focuses on an operating system independent programming with web technologies, which eliminates the need for multiple development processes.